Free Tissue Transfer Optimizes Stump Length and Functionality Following High-Energy Trauma - Piper, Merisa L.; Amara, Dominic; Zafar, Sarosh N.; Lee, Charles; Sbitany, Hani; Hansen, Scott L. (Journal of Reconstructive Microsurgery Open, 2019)
Background Advances in medicine and surgery have allowed patients, who in the past would have required more aggressive amputations, to maintain longer stump lengths. Microvascular free tissue transfer has become increasingly popular to preserve limb length and optimize functionality. We present our experience using microvascular free flap reconstruction to preserve lower extremity limb length in the setting of high-energy trauma.Methods We conducted an Institutional Review Board-approved retrospective review of patients at three San Francisco hospitals who underwent free flap reconstruction after high-energy trauma between 2003 and 2015. We included all patients who underwent free flap reconstruction for lower extremity limb length preservation. We reviewed patient demographics, preoperative variables, intraoperative details, and postoperative outcomes, including complications, functional status, reoperation rates, and need for revision amputation.Results Twelve patients underwent microvascular free tissue transfer for limb length preservation. Overall, the patients had similar preoperative comorbidities and a mean age of 44. Six patients had postoperative complications: three minor complications and three major complications. Seven patients had additional surgeries to improve the contour of the flap. One patient required revision amputation, while the remaining 11 patients preserved their original limb length. The majority of patients were fully ambulatory, and four used a prosthesis.Conclusion Microvascular free tissue transfer can be used to effectively maintain lower extremity stump length following trauma. Although these patients often require multiple surgeries and face lengthy hospital courses, this technique enables preservation of a functional extremity that would otherwise require a more proximal amputation.
Keywords: limb salvage; limb length preservation; extremity reconstruction